2022
DOI: 10.4178/epih.e2022091
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of edentulism among older adults using the Korean National Health Insurance Service database, 2013-2018

Abstract: Objectives:The worldwide aging population is rapidly accelerating. Oral diseases related to ageing are also on the rise. This study examined a trend in the incidence of edentulism among the Korean older population using data from the Korean National Health Insurance Service (KNHIS).Methods: Data on older adults, aged ≥ 75 years of age, were obtained from the KNHIS for the period 2013-2018. Edentulism was defined as a treatment history of complete dentures on the KNHIS. Exclusion criteria included both disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…According to a previous study, the edentulism incidence in older Korean adults slightly increased due to the increase in older population in Korea. 21 Moreover, Silva-Junior, et al 18 reported a higher incidence of tooth loss in older adults. Using machine learning analysis, Cooray, et al 32 showed that older people predominantly had a high prevalence of tooth loss in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous study, the edentulism incidence in older Korean adults slightly increased due to the increase in older population in Korea. 21 Moreover, Silva-Junior, et al 18 reported a higher incidence of tooth loss in older adults. Using machine learning analysis, Cooray, et al 32 showed that older people predominantly had a high prevalence of tooth loss in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Nilsson, et al 20 showed a longitudinal evaluation of tooth loss in Sweden. In Korea, Go, et al 21 showed the incidence of edentulism among older Korean adults using the National Health Insurance Service big data, and Jung 22 showed the trends in prevalence with total tooth loss in Korean adults aged 60 years and older. However, the incidence of SPE in adults aged ≥20 years has not been fully elucidated in Korea.…”
Section: Introductionmentioning
confidence: 99%